The Oxford handbook of critical management studies - Alvesson, Mats, 1956-; Bridgman, Todd.; Willmott, Hugh. (Oxford : Oxford University Press, 2011)
Critical Management Studies (CMS) has emerged as a movement that questions the authority and relevance of much mainstream thinking and practice. Critical of established practices and institutional arrangements, it challenges many orthodoxies in management and organization studies. This handbook maps the terrain of CMS today.
Originally published: 2009.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Management; Management -- Philosophy; Critical theory